2023
DOI: 10.21203/rs.3.rs-2832463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic distribution of laboratory-confirmed cases of rabies in domestic and wild animals based on passive surveillance records in Uganda: 2015-2022

Abstract: Background In Uganda, data regarding rabies outbreaks are acquired through passive surveillance. However, this surveillance system is associated with challenges such as limited case reporting and logistical gaps, leading to reduced sample submission for the positive diagnostic to the national reference veterinary laboratory. Although the dog is a main transmitter of rabies virus in low- and medium-income countries, wildlife reservoirs (e.g., mongoose, jackals, foxes) can potentially spread the virus to livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…We also think that the elevated figures of mortality are due to risk-based sampling carried out in our study, since we expect more rabies cases at the wildlife-dog-livestockhuman interface. Furthermore, our findings for livestock did not agree with the study by Omodo et al (9), which reported lower incidence of rabies in cattle and goats using laboratory specimens collected between 2015-2022 in Uganda. The discrepancy could Incidence of rabies by distance to the Pian Upe Game Reserve in Bukedea district, Eastern Uganda.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We also think that the elevated figures of mortality are due to risk-based sampling carried out in our study, since we expect more rabies cases at the wildlife-dog-livestockhuman interface. Furthermore, our findings for livestock did not agree with the study by Omodo et al (9), which reported lower incidence of rabies in cattle and goats using laboratory specimens collected between 2015-2022 in Uganda. The discrepancy could Incidence of rabies by distance to the Pian Upe Game Reserve in Bukedea district, Eastern Uganda.…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancy could Incidence of rabies by distance to the Pian Upe Game Reserve in Bukedea district, Eastern Uganda. have been brought about by differences in geographical areas, given that they picked scattered regions in the country where the risk of rabies varied greatly (9). In this study, 3% (n=9) of households reported co-occurrence of rabies in humans, livestock, and dogs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation